Metabolic effect of blocking sodium-taurocholate co-transporting polypeptide in hypercholesterolemic humans with a twelve-week course of bulevirtide: n exploratory phase I clinical trial - Stoll, Felicitas E.; Seidel-Glätzer, Andrea; Burghaus, Ina; Göring, Oliver; Sauter, Max; Rose, Peter; Daniel, Volker; Haag, Mathias; Schwab, Matthias; Riffel, Johannes; André, Florian; Taylor, Lenka A.; et al. (International journal of molecular sciences, 2022)
Bile acids (BA) play an important role in cholesterol metabolism and possess further beneficial metabolic effects as signalling molecules. Blocking the hepatocellular uptake of BA via sodium-taurocholate co-transporting polypeptide (NTCP) with the first-in-class drug bulevirtide, we expected to observe a decrease in plasma LDL cholesterol. In this exploratory phase I clinical trial, volunteers with LDL cholesterol > 130 mg/dL but without overt atherosclerotic disease were included. Thirteen participants received bulevirtide 5 mg/d subcutaneously for 12 weeks. The primary aim was to estimate the change in LDL cholesterol after 12 weeks. Secondary endpoints included changes in total cholesterol, HDL cholesterol, lipoprotein(a), inflammatory biomarkers, and glucose after 12 weeks. In addition, cardiac magnetic resonance imaging (CMR) was performed at four time points. BA were measured as biomarkers of the inhibition of hepatocellular uptake.